DkMYB14 is a bifunctional transcription factor that regulates the accumulation of proanthocyanidin in persimmon fruit. (24th May 2021) - Chen, Wenxing; Zheng, Qingyou; Li, Jinwang; Liu, Ying; Xu, Liqing; Zhang, Qinglin; Luo, Zhengrong
SUMMARY: Proanthocyanidins (PAs) are phenolic secondary metabolites that contribute to the protection of plant and human health. Persimmon ( Diospyros kaki Thunb.) can accumulate abundant PAs in fruit, which cause a strong sensation of astringency. Proanthocyanidins can be classified into soluble and insoluble PAs; the former cause astringency but the latter do not. Soluble PAs can be converted into insoluble PAs upon interacting with acetaldehydes. We demonstrate here that DkMYB14, which regulates the accumulation of PA in persimmon fruit flesh, is a bifunctional transcription factor that acts as a repressor in PA biosynthesis but becomes an activator when involved in acetaldehyde biosynthesis. Interestingly, both functions contribute to the elimination of astringency by decreasing PA biosynthesis and promoting its insolubilization. We show that the amino acid Gly39 in the R2 domain and the ethylene response factor‐associated amphiphilic repression‐like motif in the C‐terminal of DkMYB14 are essential for the regulation of both PA and acetaldehyde synthesis. The repressive function of DkMYB14 was lost after the mutation of either motif, and all activities of DkMYB14 were eliminated following the mutation of both motifs. Our results demonstrate that DkMYB14 functions as both a transcriptional activator and a repressor, directly repressing biosynthesis of PA and promoting its insolubilization, resulting in non‐astringency in persimmon. Significance Statement: DkMYB14 is a bifunctional transcription factor that reduces the accumulation of soluble proanthocyanidin (PA) in persimmon fruit by negatively regulating PA biosynthesis and positively regulating PA insolubilization, resulting in non‐astringency.